The Effect of Traditional Local Games on Development of Gross Motor Skills in Children with Mental Retardation - Hasan Baghande; Elahe Arab Ameri; Foad Niknasab (University of Tehran, 2016)
The aim of this study was to investigate the effect of traditional - local games on the development of gross motor skills of children with educable mental retardation. 30 educable mentally retarded children in Welfare Organization of Marivan city (mea age 12.8 ±1.12 yr and IQ 33.61±7.81) were studied with purposive sampling method. All children were pretested; then, samples were randomly divided into two groups: control and experimental. Each group consisted of 8 boys and 7 girls. In gross motor skills, Bruininks - Oseretsky test of Motor Proficiency was used. Traditional - local games were practiced by the experimental group during 32 sessions, each session 50-60 minutes for 4 days a week. The control group performed their daily routine. After 32 sessions of practice, both groups were post-tested. To study the research hypotheses, non-parametric Wilcoxon and U Mann Whitney tests were used (SPSS16). The results showed a significant difference in posttest scores between the two groups (P<0.05). The experimental group had higher scores. The findings suggested that the training program used (traditional - local games) in this study was appropriate to improve the gross motor skills in educable mentally retarded children and can be used as a training program in training centers.